Lubna and Pebble - Meddour, Wendy (Dial Books for Young Readers, 2019)
"Lubna's best friend is a pebble. Pebble always listens to her stories. Pebble always smiles when she feels scared. But when a lost little boy arrives in the World of Tents, Lubna realizes that he needs Pebble even more than she does." -- From dust jacket.